Navigating stakeholder communication: Organizational sensemaking in educational consultancy - Reyes, Angel Marie (Animo Repository, 2023)
Drawing upon Karl Weick's sensemaking framework, the study explores how members of Quality Education Online Management (QEOM), an educational consulting company, construct meaning to reduce ambiguity and uncertainty in communicating with their stakeholders—parents, schools administrators, and educational authorities. The study utilized semi-structured interviews to gather data from participants (n=10) and implemented thematic analysis. Several accounts of conflict with clients regarding issues about admissions and policies, program information, and managing client expectations, processing and problem-solving revealed that QEOM has not established consensus in the manner and approach of communicating with their stakeholders and reducing equivocality. To resolve the ambiguity in their information environment, the study proposes strategic practices such as establishing a communication manual, standard operating procedures, a centralized record system, and consistent alignment meetings. The research findings offer practical insights for educational consultant organizations like QEOM in developing strategies for addressing conflicts, implementing strategic decision-making, and navigating stakeholder communication. Keywords: Organizational sensemaking, stakeholder communication, educational consultancy, information environments, equivocality